Renal blood oxygenation level-dependent magnetic resonance imaging to measure renal tissue oxygenation: a statement paper and systematic review. (23rd August 2018) - Pruijm, Menno; Mendichovszky, Iosif A; Liss, Per; Van der Niepen, Patricia; Textor, Stephen C; Lerman, Lilach O; Krediet, C T Paul; Caroli, Anna; Burnier, Michel; Prasad, Pottumarthi Vara
Abstract: Tissue hypoxia plays a key role in the development and progression of many kidney diseases. Blood oxygenation level-dependent magnetic resonance imaging (BOLD-MRI) is the most promising imaging technique to monitor renal tissue oxygenation in humans. BOLD-MRI measures renal tissue deoxyhaemoglobin levels voxel by voxel. Increases in its outcome measure R2* (transverse relaxation rate expressed as per second) correspond to higher deoxyhaemoglobin concentrations and suggest lower oxygenation, whereas decreases in R2* indicate higher oxygenation. BOLD-MRI has been validated against micropuncture techniques in animals. Its reproducibility has been demonstrated in humans, provided that physiological and technical conditions are standardized. BOLD-MRI has shown that patients suffering from chronic kidney disease (CKD) or kidneys with severe renal artery stenosis have lower tissue oxygenation than controls. Additionally, CKD patients with the lowest cortical oxygenation have the worst renal outcome. Finally, BOLD-MRI has been used to assess the influence of drugs on renal tissue oxygenation, and may offer the possibility to identify drugs with nephroprotective or nephrotoxic effects at an early stage. Unfortunately, different methods are used to prepare patients, acquire MRI data and analyse the BOLD images. International efforts such as the European Cooperation in Science and Technology (COST) action 'Magnetic Resonance Imaging Biomarkers for Chronic Kidney Disease' (PARENCHIMA) are aiming to harmonize this process, to facilitate the introduction of this technique in clinical practice in the near future. This article represents an extensive overview of the studies performed in this field, summarizes the strengths and weaknesses of the technique, provides recommendations about patient preparation, image acquisition and analysis, and suggests clinical applications and future developments.